Pembinaan Olimpiade Matematika Bagi Siswa SMP Mojokerto Berbasis Problem Solving - Rosyadi, Alfiani Athma Putri; Utami, Octavina Rizky Putri; Syaifuddin, Mohammad (Abdimas Mandalika, 2026)
Abstract: Low student motivation and school facilities for Olympic coaching are the main problems of this activity. Therefore, the purpose of this community service is to provide intensive periodic coaching in mathematics for junior high school students in Mojokerto based on problem solving, which is to provide a strong foundation for students to excel in academic competitions. The implementation of this program will be divided into five main stages that are interconnected. The five stages are socialization, training, technology application, mentoring and evaluation, and program sustainability. The results of the mentoring activities obtained data that this activity has improved students' mathematical competence. This can be seen from the pretest and post-test results after the program implementation. The suggestion for the next community service is the need for an Olympiad club for program sustainability. In addition, collaboration with several agencies, such as the education office and universities, is also needed to maximize the activities.Abstrak: Rendahnya motivasi siswa dan fasillitas sekolah untuk pendampingan olimpiade menjadi permasalahan utama dari kegiatan ini. Oleh karena itu, tujuan dari pengabdian masyarakat ini adalah memberikan pembinaan intensif berkala olimpiade matematika bagi siswa SMP mojokerto berbasis problem solving" Kegiatan ini memberikan fondasi yang kuat bagi siswa untuk unggul dalam kompetisi akademik. Pelaksanaan program ini  dibagi menjadi lima tahapan utama yang saling berkesinambungan. Kelima tahapan tersebut adalah sosialisasi, pelatihan, penerapan teknologi, pendampingan dan evaluasi, serta keberlanjutan program. Hasil pelaksanaan pendampingan kegiatan pengabdian diperoleh data bahwa kegiatan ini sudah meningkatkan kompetensi matematiks siswa. Hal ini dapat dilihat dari hasil pretes dan postest setelah pelaksanaan program.